Sufficiency-driven business models for rare earth recycling: integrating stakeholder collaboration and customer discovery for sustainable innovation - Chinenye Chinwego; Rosanna Garcia; Daniel McArthur Sehar; Evan MacGregor; Steven Tate; Kenneth Savage; Thaddaeus Zuber; Benjamin Sseruwagi; Daniel Dietrich; Emmanuel Opoku; David Smith; Adam Powell; et al. (Journal of Innovation and Entrepreneurship, 2025)
Abstract This paper explores the development of a collaborative and customer-centric business model for sustainable innovation in rare earth magnet recycling. Rare earth elements have become crucial to various electronics and renewable energy systems. Due to their finite nature and the supply risk they pose as they are available in a few countries, recycling these magnets is becoming increasingly important as demand increases. This study highlights the importance of developing business models that prioritize resource sufficiency, economic viability and environmental conservation. It emphasizes customer discovery, a critical component in understanding market needs and consumer behavior. Through detailed case studies as part of the NSF I-Corps program, this paper presents evidence from over 130 stakeholder interviews, completed with individuals from rare earth magnet companies, rare earth magnet recycling companies, National laboratories, metal alloy companies, and metal recycling companies. These case studies highlight best practices, challenges, and lessons learned, providing a comprehensive blueprint for other businesses to follow. In addition, this paper explores policy implications, advocating for regulatory frameworks that support sustainable practices and incentivize recycling initiatives. Ultimately, this research aims to contribute to the circular economy by demonstrating how sufficiency-driven business models can lead to sustainable growth and resilience in the rare earth recycling industry. By integrating stakeholder collaboration and customer discovery, businesses can innovate effectively, ensuring the sustainability of both their operations and the environment.